PENYULUHAN DAN PELATIHAN PEMBUATAN TUMPENG UPAKARA SEBAGAI UPAYA PENINGKATAN PENDAPATAN UKM UPAKARA DI DESA PED KECAMATAN NUSA PENIDA KLUNGKUNG - Ni Luh Adisti Abiyoga Wulandari; Ni Komang Sumadi; Made Dian Agustina; Putu Deddy Samtika Putra (JURNAL SEWAKA BHAKTI, 2022)
This Upakara UKM is located in Ped Village, Nusa Penida District and has been running for 7 years by serving various types of ceremonies in Nusa Penida. In running her business, Mrs. Nyoman Sukerti invites six workers from her village as well as her neighbors who do not have jobs to help her in producing various types of ceremonies. The production process of the ceremony is strongly influenced by the number of days of Hindu celebrations. In producing the ceremony, many upakara materials are needed, one of which is tumpeng and penek. Tumpeng and Penek are one of the materials used in the manufacture of ceremonies or offerings. Almost all of the offerings used in religious ceremonies use tumpeng and penek so it can be said that this product is one of the main ingredients in the manufacture of upakara/banten. The Balinese themselves have recently become accustomed to buying ready-made ceremonial facilities. Moreover, some Hindus have other activities, so they prefer to buy ready-made facilities such as tumpeng and penek. Counseling and training on the making of tumpeng and pencak is given in community service activities. By understanding the process of making tumpeng and penek well, it is hoped that in the future this business will be able to produce tumpeng and penek to meet the needs of ceremony materials in Nusa Penida District. This service activity also provides counseling on marketing strategies so that it is hoped that in the future it will be able to market Tumpeng and Penek products that are produced very well through social media that are currently developing. With this counseling and training, it is hoped that the UKM Upakara Mrs. Nyoman Sukerti will continue to develop and progress, which of course will have an impact on increasing income.